“God, the King and Our Chiefs”: The concept of “order” in the Real Felipe del Callao (1824-1826) - Castro Olivas, Jorge Luis (2021)
This paper reflects on the official royalist political discourse in the fortress of Real Felipe del Callao, between 1824 and 1826, focusing particularly on the concept of "order" and its expression in the official royalist press organs, public announcements and proclamations of the governor José Ramón Rodil y Campillo. This concept was related to a mental framework of the Old Regime, in which terms such as "nation", "Spanish nation" and others aimed to generate a representation that sought to evoke feelings of identity and identification that revolved around a set of networks of meaning and mental structures that became the ideological justification needed by the besieged to continue facing the many sufferings and deprivations that overwhelmed them day by day and that kept them in their fortresses to the limit of their resistance.